Saeed’s, the protagonist, character in a comparative analysis in: Saeed Abi Al-Nahs the Pessoptimist “Al Mutasha’l” (Habibi, 2006) and Guardian of the Lost City “Haris Al Madena Ad Die’aa” (Nasrallah, 1998) novels - Al-Osaili, Eiad Fathi Mousa; AL-Hajaya, Atalla Raja Mohammad; Ibrahim, Abdullah Mahmod Ahmad; Almajali, Hasan Mutleb Mohammed; Najjar, Afnan Abdul Fattah Musleh; Shalan, Sanaa Kamel Ahmad (Research Journal in Advanced Humanities, 2023)
This study presents a depiction of the character of the protagonist (Saeed) in two contemporary novels, Saeed Abi Al-Nahs the Pessoptimist by Emile Habibi, first published in 1974 (Habibi, 1997), and (The Guardian of the Lost City) by Ibrahim Nasrallah (Nasrallah). Both are contemporary Palestinian novelists. The first lived most of his life, died, and was buried in occupied Palestine; the second lived most of his life in Jordan, and is still alive. Saeed’s character in the two novels plays the heroic role, who suffers from his own crises that shape his relationships in society as well as his perception of the difficult reality he lives in. This study presents a comparison between these two ambiguous personalities who present a special perception of unhappiness, anxiety, sadness, and falling into historical ambiguities and life circumstances. This comparison was made by examining the following aspects: An introduction to Saeed’s character in the two novels: Saeed Abi Al-Nahs the Pessoptimist and the Guardian of the Lost City, Saeed character in The Strange Facts in the Disappearance of Saeed, Abi Al-Nahs the Pessoptimist, Symbolism of Saeed Abi Al-Nahs the Pessoptimist character, Saeed Abi Al-Nahs the Pessoptimist who represents Emile Habibi, character formation of Saeed Abi Al-Nahs The Pessoptimist, the fateful fate of Saeed in Saeed Abi Al-Nahs the Pessoptimist, irony and ambiguity in The Guardian of the Lost City title, Saeed the Guardian of the Lost City, Saeed’s journey in his city in The Guardian of the Lost City, and finally, a conclusion and results.